DAYA TAMPUNG TAMAN MACAN SEBAGAI TAMAN KOTA DALAM PEMANFAATAN FUNGSI WISATA DI KOTA MAKASSAR - Muhammad Musawantoro; Masri Ridwan (JAMBURA GEO EDUCATION JOURNAL, 2020)
The importance of this research is a description of the maximum capacity of a tourist area, to sustain the urban forest which has many functions for urban communities, seeing an increase in the population of 3.7% and activities around the urban forest area in Makassar, it is necessary to study the maximum capacity, the study was conducted with a qualitative method with a survey approach, the results of the study explained that the urban forest was known as the Macan Park assuming operating hours for 8 hours, then for urban forest or tiger park, Makassar City is PCC = 4,900 m2 / 65 m2 x 4. Then the maximum number of visitors can be obtained per day is + 302 people with the number of needs per person long enjoying a 2-hour visit. The conclusion of the importance of the application of a maximum capacitance in an area is to support the sustainability of the area with a conservation approach